The Relationship Between The Level Of Training Of Paramedics In Psychological First Aid And Reducing Trauma Among Injured People (The Review of Diabetic Studies, 2025)
This study aims to examine the relationship between the level of training of paramedics in psychological first aid and its role in reducing psychological trauma among injured people in the Kingdom of Saudi Arabia. The descriptive analytical approach was adopted using the questionnaire tool to collect data from a sample of (200) participants from the paramedics working in the Saudi Red Crescent Authority. The results showed a strong positive relationship between the level of training and the effectiveness of intervention in reducing psychological trauma. They also indicated that training explains a significant proportion of the variance in reducing the severity of trauma, in addition to the presence of statistically significant differences in favor of paramedics who received specialized training, as well as between different levels of experience. These results underscore the importance of investing in psychological training programs for paramedics to enhance the quality of care and improve the mental health of injured patients.